Gas exchange and morphometric characteristics of basil according to the times and collection positions in the plant - Coutinho, Pablo Wenderson Ribeiro; Echer, Márcia de Moraes; Guimarães, Vandeir Francisco; Bulegon, Lucas Guilherme; Abade, Mayra Taniely Ribeiro; Rocha, Maria Eunice Lima (Scientia Agraria Paranaensis, 2022)
The productive potential of plant species depends on the genotype versus environment interaction, so the choice of cultivar is decisive for the success of the crop. Thus, the objective of this work was to evaluate the levels of photosynthetic pigments and morphometric characteristics of two cultivars of green and red basil as a function of the collection time and different collection positions in the plant, as well as the gas exchange in response to variation of the flux density of photosynthetically active photons. The experiment was carried out in a protected environment with a randomized block design in a 2 x 3 x 3 factorial scheme containing 2 treatments consisting of two basil cultivars (alfavaca basilicão, red and green) and fifteen replications. The first factor was constituted by the cultivars, the second, by the time of collection, and the third, by the positions in which the collections were carried out on the plant. For evaluations of morphometric variables and gas exchange rates, the two cultivars were compared. Basil has photosynthesis saturation at radiation rates of about 1500 μmol m-2 s-1. The green colored cultivar was more productive, in addition to having the highest levels of chlorophyll a, b and total, and lower rate of leaf transpiration in response to photosynthetically active photons flow density, adapted for greater carboxylation efficiency and water use.